1996
DOI: 10.1063/1.361132
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of antimony-based skutterudites

Abstract: Articles you may be interested inPlasma dispersion effect in heavily doped antimony-based passive optical waveguides Appl. Phys. Lett. 92, 203508 (2008); 10.1063/1.2936298 Two-dimensional photonic crystals in antimony-based films fabricated by holography -earth ions occupy the voids in the skutterudite structure. These void-filling ions interact with some of the lattice vibrations in this structure and produce a shift and broadening of the observed lines. The most prominent lines in all of the samples are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 24 publications
(38 reference statements)
6
42
1
Order By: Relevance
“…This means that the size of the unit cell is determined mainly by the covalent connection in the Co-(Sb,Ge) host network. Similar behavior was observed for the lattice constants of LnRh 4 Sb 9 Ge 3 , Ln = La, Ce, Pr, and Nd [10]. The lattice constants for those Rh compounds were in a very narrow range from 9.112 to 9.107 Å.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…This means that the size of the unit cell is determined mainly by the covalent connection in the Co-(Sb,Ge) host network. Similar behavior was observed for the lattice constants of LnRh 4 Sb 9 Ge 3 , Ln = La, Ce, Pr, and Nd [10]. The lattice constants for those Rh compounds were in a very narrow range from 9.112 to 9.107 Å.…”
Section: Resultssupporting
confidence: 60%
“…Nolas et al reported the first filled skutterudite compounds containing group 14 elements in the M site, LnIr 4 Sb 9 Ge 3 , Ln = La, Nd, and Sm. In these compounds, the electrons from the guest trivalent cations compensate for the electron deficiency of the host network caused by the substitution of a group 14 element for the group 15 element [10][11][12]. We also prepared a series of Ge-substituted filled skutterudite compounds LnRh 4 Sb 9 Ge 3 , Ln = La, Ce, Pr, and Nd, using high-pressure and high-temperature reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…The values listed in Table I as volumes are consistent with those previously reported. 12,16,17) The X-ray diffraction experiments under high pressures, using synchrotron radiation, were performed at the beamline BL-18C at the KEK Photon Factory (Tsukuba, Japan). The incident beam was monochromatized by Si(111) double crystals.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding unfilled skutterudites are similarly classified; an unfilled skutterudite RhP 3 , which corresponds to La 0.6 Rh 4 P 12 , has been experimentally determined to be a metal [20,21]. RhAs 3 and RhSb 3 , which correspond to La 0.5 Rh 4 As 12 and La 0.5 Rh 4 Sb 12 , respectively, are semiconductors with E g > 0.85 eV [22] and E g = 0.8 eV [23,24], respectively. Thus, La 0.5 Rh 4 As 12 and La 0.5 Rh 4 Sb 12 not only have similar electrical properties, but also exhibit similar changes in the electrical properties as a result of La filling.…”
Section: Discussionmentioning
confidence: 99%